The impacts of production and price shocks on the coffee industry in PNG - Arua, Stanley; Gondo, Robert; Kinau, Adrian; Kotto, Aaron; Dorosh, Paul A.; Schmidt, Emily; Tian, Junyan (International Food Policy Research Institute, 2024)
Coffee is one of Papua New Guinea’s leading agricultural export in value terms, accounting for 156 million USD of export earnings in 2021 (FAOSTAT, 2023), 13 percent of agricultural export revenues and 1.4 percent of total export revenues. The coffee industry is a major source of income for some 2.5 million people, mainly in farm households, and is cultivated in 17 out of 22 provinces (ACIAR, 2021). Coffee exports and incomes are threatened, however, by a number of supply side factors such as ageing coffee trees, outbreaks of coffee berry borer, poor production practices and challenges in reaching markets (i.e. transport and post-harvest handling), as well as by demand-side fluctuations in the world price of coffee (World Bank, 2022; Dorum et al., 2023). This research note first presents an overview of PNG’s coffee sector, including a discussion of production trends and structure of the coffee value chain. We then utilize a simple partial equilibrium model of coffee supply and demand, along with data on coffee production and household consumption from the PNG Household Income and Expenditure Survey (HIES) of 2009/10, FAOSTAT and the World Bank, to simulate the impacts of potential production and price shocks on the coffee industry in Papua New Guinea (PNG). Finally, we present an analysis of price movements in recent years and the potential costs and benefits of a price stabilization policy for coffee producers.